After the Flood - J. Pryor (Law Text Culture, 2008)
When the World Trade Centre was destroyed in New York on 11 September 2001, I felt devastation for all the victims of this atrocity. This included the terrorist themselves as well as the families of the dead and injured and of the perpetrators. When America used this atrocity as a reason to attack Iraq I was very disturbed by the transposition of lines of blame to a country that had no direct link to this attack on the USA.